SYSTEMIC EFFECTS OF LOCAL PRODUCTIONOFPRO- AND ANTI-FIBROGENIC MEDIATORS IN PERITONEAL DIALYSIS PATIENTS - N. Stepanova; O. Burdeyna; V. Driyanska; V. Savchenko; M. Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2016)
Peritonealfibrosis (PF) is a common morphological change in peritoneal dialysis (PD) patients. With the progression of PF, peritoneal membrane function is impaired, which leads to ultrafiltration failure. Results of studies in recent years show the crucial role of high production monocytic chemoattractant protein -1 (MCP-1) of peritoneal fibrosis in PD-patients. The aim was to determine intraperitoneally production ofIL-10 and MCP-1 and its relationship with clinical and laboratory parameters of adequacy of dialysis.Patients and methods. A prospective observational study involved 18patients with CKD stage Vwith non-diabetic nephropathy, were treated with continuous ambulatory peritoneal dialysis (PAPD). The limits of the normal range (reference range) were obtained from the survey results of 10 conditionally healthy individuals. ELISA method in serum and peritoneal dialysis effluent (PDE) investigated levels ofIL-10 and MSP-1. PAPD adequacy indicators evaluated by determining the concentration of urea and creatinine in plasma, urine and dialysate, calculated weekly creatinine clearance (CrCl), dialysis (Ш/ Vd), renal (Ш / Vr) and шА weekly urea clearance (Kt/ V). nmstep@ukr.net Results. In all of the PD-patients compared to healthy donors conventionally, there was a significant increase in concentration of the cytokines. We determined the positive regression relationship between the concentration of MCP-1 and IL-10 in PDE and the level of total weekly (Kt / V) and renal (Kt / Vr).Conclusions. We determined the regression dependence, which allowed to identify clinical parameters that are most closely (statistically significant) related to intraperitoneal production of MCP-1 and IL-10.